Method for producing optical film with pressure-sensitive adhesive layer

The adhesive film, utilizing a pressure-sensitive adhesive composition with butyl acrylate, hydroxyl group-containing monomers, and isocyanate compounds, addresses the challenges of achieving high adhesion and durability in thin adhesive layers for optical members, eliminating the need for aging treatments and surface modifications.

JP7663638B2Active Publication Date: 2025-04-16ZACROS CORP
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2023135361
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-04-16
Estimated Expiration
2034-08-06

AI Technical Summary

Technical Problem

Existing adhesive films used for bonding optical members, such as polarizers, face challenges in achieving high adhesion performance and durability while maintaining a thin adhesive layer, which is necessary for thinner optical members. Additionally, these films often require aging treatment and surface modifications like corona treatment to enhance adhesion, which can be inefficient.

Method used

A pressure-sensitive adhesive composition is developed, characterized by the use of butyl acrylate as the essential monomer, combined with a hydroxyl group-containing copolymerizable vinyl monomer and an isocyanate compound as a crosslinking agent. This composition forms an adhesive layer with a high gel fraction, excellent flexibility, rigidity, durability, and reworkability, without the need for extensive aging treatment.

Benefits of technology

The adhesive film achieves high adhesion performance and durability, maintaining strength even after exposure to high temperature and high humidity conditions. It exhibits excellent reworkability and does not require surface treatments like corona treatment, making it suitable for thin optical member applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663638000001
    Figure 0007663638000001
  • Figure 0007663638000002
    Figure 0007663638000002
  • Figure 0007663638000003
    Figure 0007663638000003
Patent Text Reader

Abstract

To provide a method for manufacturing an adhesive layer-attached optical film that enables formation of an adhesive layer having excellent reworkability and high adhesion performance despite its thinness.SOLUTION: An acrylic polymer is a copolymer obtained by copolymerizing (A) a total of 100 pts.wt. of a monomer group consisting of alkyl (meth)acrylate monomers having C1-C14 alkyl groups and (meth)acrylate monomers having aromatic groups and (B) 0.1 to 3.5 pts.wt. of hydroxyl group-containing copolymerizable vinyl monomers, without including carboxyl group-containing copolymerizable vinyl monomers or amino group-containing (meth)acrylates, the copolymer having an acid value of 0.1 or less and a weight average molecular weight of 1 million or more. The polymer contains butyl acrylate of at least 30 pts.wt., and further contains an isocyanate compound of 0.01 to 0.8 pt.wt., and a silane coupling agent of 0.01 to 0.5 pt.wt.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive composition and a pressure-sensitive adhesive film used for bonding optical members such as polarizing plates. [Background technology]

[0002] 2. Description of the Related Art Various pressure-sensitive adhesive films have been proposed for bonding optical members such as polarizing plates and retardation plates to adherends such as liquid crystal cells via pressure-sensitive adhesive layers (see, for example, Patent Documents 1 and 2). Patent Document 1 describes an optical pressure-sensitive adhesive composition that contains butyl acrylate or the like as a main monomer component and also contains an acrylamide compound or the like. Patent Document 2 describes an optical pressure-sensitive adhesive composition that contains a (meth)acrylate having an alkyl group with 4 to 8 carbon atoms as a main component monomer, a carboxyl group-containing monomer, and a nitrogen-containing vinyl monomer. Furthermore, various pressure-sensitive adhesive films have been proposed that have been devised to increase the refractive index of the pressure-sensitive adhesive layer (see, for example, Patent Documents 3 to 8). Patent Document 3 describes an optical pressure-sensitive adhesive composition that contains a tackifier having an aromatic ring and a refractive index of 1.51 to 1.75. Patent Document 4 describes a pressure-sensitive adhesive sheet containing a pressure-sensitive adhesive composition that contains a copolymerizable polymer of an acrylic acid-modified monomer that contains an aromatic ring. Patent Document 5 describes an optical pressure-sensitive adhesive composition containing a tackifier resin having an aromatic ring and an aromatic phosphate ester plasticizer. Patent Document 6 describes a pressure-sensitive adhesive obtained by curing a pressure-sensitive adhesive composition that contains an acrylic resin and an aromatic compound having one ethylenically unsaturated group. Patent Document 7 describes an optical component in which a retardation film and a birefringent plate are fixed to each other via an acrylic adhesive containing an aromatic monomer. Patent Document 8 describes a pressure-sensitive adhesive composition containing a urethane resin obtained by reacting an aromatic diisocyanate with an aromatic polyester diol. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2012-177022 A [Patent Document 2] JP 2012-201734 A [Patent Document 3] JP 2007-084762 A [Patent Document 4] JP 2011-153169 A [Patent Document 5] JP 2012-167188 A [Patent Document 6] JP 2012-021148 A [Patent Document 7] JP 2006-293281 A [Patent Document 8] JP 2009-091522 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, a requirement for pressure-sensitive adhesive films used for bonding layers of optical components has been to make the thickness of the pressure-sensitive adhesive layer thinner in order to facilitate the thinning of optical components. Generally, the adhesive strength of a pressure-sensitive adhesive layer is approximately proportional to the thickness of the pressure-sensitive adhesive layer, and therefore, when the thickness of the pressure-sensitive adhesive layer is reduced, the adhesive strength decreases accordingly.

[0005] However, in recent years, adhesive films have been required to have adhesive strength equivalent to that of conventional adhesive films (with thick adhesive layers of approximately 30 μm) even when the thickness of the adhesive layer is reduced, and also to have durability equivalent to or greater than that of conventional adhesive films when left in high temperature and high humidity environments for long periods of time. Furthermore, because it is possible to make the adhesive layer thinner and to form an adhesive layer that does not require aging treatment (curing at a constant temperature), there is a demand for an NCF (Non Carrier Film) configuration consisting of only the adhesive layer, omitting the adhesive film substrate, and having a component structure of "release film / adhesive layer / release film."

[0006] Furthermore, in conventional pressure-sensitive adhesive films, an aging treatment is carried out after the pressure-sensitive adhesive film is attached to an adherend, which makes it possible to improve the adhesion between the adherend and the pressure-sensitive adhesive layer. However, in the case of NCF-type PSA films, the adhesive layer has already been aged, so the adhesive strength between the adherend and the adhesive layer is insufficient, and therefore there is a problem in that the surface of the adherend needs to be subjected to a surface treatment such as a corona treatment. What is needed is a self-adhesive film that overcomes these requirements and problems.

[0007] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a pressure-sensitive adhesive composition capable of forming a pressure-sensitive adhesive layer that has excellent reworkability and high adhesion performance despite being a thin film, and a pressure-sensitive adhesive film using the same. [Means for solving the problem]

[0008] In order to solve the above problems, the pressure-sensitive adhesive composition of the present invention is characterized in that it uses butyl acrylate as an essential monomer, does not use a carboxyl group-containing copolymerizable vinyl monomer as a functional group-containing monomer, but uses a hydroxyl group-containing copolymerizable vinyl monomer, and has a weight-average molecular weight of 1,000,000 or more, and further uses an isocyanate compound as a crosslinking agent, and more preferably uses a silane coupling agent in combination with the copolymer.

[0009] In order to solve the above problems, the present invention provides a pressure-sensitive adhesive composition comprising: (1) an acrylic polymer which is a copolymer having an acid value of 0.1 or less and a weight average molecular weight of 1,000,000 or more, the acrylic polymer comprising, as a main component (meth)acrylate monomer, at least one selected from the group consisting of alkyl (meth)acrylate monomers having an alkyl group carbon number of C1 to C14 and (meth)acrylate monomers having an aromatic group, and which contains at least 30 parts by weight or more of butyl acrylate out of a total of 100 parts by weight of the main component (meth)acrylate monomers, and which does not contain a carboxyl group-containing copolymerizable vinyl monomer, (2) 0.1 to 3.5 parts by weight of a hydroxyl group-containing copolymerizable vinyl monomer relative to a total of 100 parts by weight of the main component (meth)acrylate monomers, and which has an acid value of 0.1 or less and a weight average molecular weight of 1,000,000 or more; and (3) 0.01 to 0.8 parts by weight of an isocyanate compound as a crosslinking agent relative to a total of 100 parts by weight of the main component (meth)acrylate monomers.

[0010] Furthermore, it is preferable that (4) a silane coupling agent is contained in an amount of 0.01 to 0.5 parts by weight based on 100 parts by weight of the total of the (meth)acrylate monomers as the main component.

[0011] The isocyanate compound is preferably a trimethylolpropane adduct of tolylene diisocyanate.

[0012] In addition, the (2) hydroxyl group-containing copolymerizable vinyl monomer is preferably at least one selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate.

[0013] The present invention also provides a pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition, the pressure-sensitive adhesive layer having a gel fraction of 40 to 75% after crosslinking and an adhesive strength of a 25 μm-thick pressure-sensitive adhesive layer of 1.5 to 6.0 N / 25 mm.

[0014] In addition, it is preferable that the adhesive layer, after being attached to an adherend, has an adhesive strength of 1.5 to 10 N / 25 mm after being stored at 70° C. for 10 days.

[0015] The present invention also provides a pressure-sensitive adhesive film comprising the pressure-sensitive adhesive layer laminated on one surface of a substrate.

[0016] The present invention also provides an adhesive film which is used for bonding a polarizing plate and a display panel, and which uses the adhesive film.

[0017] The present invention also provides the pressure-sensitive adhesive layer used as a pressure-sensitive adhesive layer of a pressure-sensitive adhesive layer-attached polarizing plate.

[0018] The present invention also provides the pressure-sensitive adhesive layer used as a pressure-sensitive adhesive layer of a pressure-sensitive adhesive layer-attached polarizing plate in which a retardation film having a retardation of λ / 4 or λ / 2 is used as a constituent material of the polarizing plate.

[0019] The present invention also provides a pressure-sensitive adhesive layer-attached optical film, comprising an optical film and the pressure-sensitive adhesive layer laminated on at least one surface of the optical film. Effect of the Invention

[0020] According to the present invention, a pressure-sensitive adhesive layer having a high gel fraction after crosslinking can be obtained while reducing the amount of crosslinking agent and the amount of functional groups compared to conventional pressure-sensitive adhesive layers, and thus a pressure-sensitive adhesive layer having flexibility, rigidity, durability, and reworkability, and a pressure-sensitive adhesive film using the same can be obtained. The pressure-sensitive adhesive film of the present invention has excellent reworkability and high adhesiveness, despite its thinness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present invention will be described below based on preferred embodiments. The pressure-sensitive adhesive composition of the present invention is characterized in that it contains (1) as a main component (meth)acrylate monomer, at least one selected from the group of monomers consisting of alkyl (meth)acrylate monomers having an alkyl group carbon number of C1 to C14 and (meth)acrylate monomers having an aromatic group, and contains at least 30 parts by weight or more of butyl acrylate out of a total of 100 parts by weight of the main component (meth)acrylate monomers, and does not contain a carboxyl group-containing copolymerizable vinyl monomer, (2) 0.1 to 3.5 parts by weight of a hydroxyl group-containing copolymerizable vinyl monomer relative to a total of 100 parts by weight of the main component (meth)acrylate monomers, and is an acrylic polymer which is a copolymer having an acid value of 0.1 or less and a weight average molecular weight of 1,000,000 or more, and (3) 0.01 to 0.8 parts by weight of an isocyanate compound as a crosslinking agent relative to a total of 100 parts by weight of the main component (meth)acrylate monomers.

[0022] In the pressure-sensitive adhesive composition according to the present invention, examples of the alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C14 include at least one of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, cyclopentyl (meth)acrylate, and cyclohexyl (meth)acrylate. The alkyl group of the alkyl (meth)acrylate monomer may be linear, branched, or cyclic. Of the total 100 parts by weight of the (meth)acrylate monomers of the main component, the total of the alkyl (meth)acrylate monomers having an alkyl group with a carbon number of C1 to C14 is preferably 70 parts by weight or more, and may be 100 parts by weight. The ratio of the alkyl (meth)acrylate monomers having an alkyl group with a carbon number of C1 to C14 to 100 parts by weight of the acrylic polymer (copolymer) of the pressure-sensitive adhesive composition is preferably 50 to 99.9 parts by weight. In the present invention, butyl acrylate is an essential monomer. Of the total 100 parts by weight of the (meth)acrylate monomers of the main component, it is preferable that at least 30 parts by weight or more of butyl acrylate is contained. Furthermore, in the present invention, the pressure-sensitive adhesive composition contains 20 parts by weight or more of methyl acrylate monomer out of a total of 100 parts by weight of (meth)acrylate monomers as the main component, which are one or more alkyl (meth)acrylate monomers having an alkyl group with a carbon number of C1 to C14, thereby making it possible to increase the refractive index of the pressure-sensitive adhesive layer to 1.47 or more.

[0023] The adhesive composition according to the present invention may further contain one or more (meth)acrylate monomers having an aromatic group as the main component (meth)acrylate monomer. Examples of the (meth)acrylate monomer having an aromatic group include benzyl (meth)acrylate, naphthyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxybutyl (meth)acrylate, 2-(1-naphthyloxy)ethyl (meth)acrylate, 2-(2-naphthyloxy)ethyl (meth)acrylate, 6-(1-naphthyloxy)hexyl (meth)acrylate, 6-(2-naphthyloxy)hexyl (meth)acrylate, 8-(1-naphthyloxy)octyl (meth)acrylate, and 8-(2-naphthyloxy)octyl (meth)acrylate. In order to obtain an adhesive layer having a high refractive index, it is preferable to blend at least one (meth)acrylate monomer having an aromatic group.

[0024] By mixing these (meth)acrylate monomers having an aromatic group with an alkyl (meth)acrylate monomer having a carbon number of C1 to C14 in the alkyl group, which is the main monomer, the refractive index of the obtained pressure-sensitive adhesive layer can be increased and adjusted, and the refractive index difference between optical members can be reduced, and total reflection can be reduced, thereby improving the total light transmittance. In the pressure-sensitive adhesive layer according to the present invention, when the pressure-sensitive adhesive composition contains a (meth)acrylate monomer having an aromatic group, it is preferably contained in a proportion of 5 to 30 parts by weight out of a total of 100 parts by weight of the main (meth)acrylate monomer. In addition, by copolymerizing a (meth)acrylate monomer having an aromatic group, the refractive index of the adhesive layer can be increased even further than the effect of increasing the refractive index of the adhesive layer by including 20 parts by weight or more of methyl acrylate monomer out of a total of 100 parts by weight of the above-mentioned main component (meth)acrylate monomers. As described above, there are two methods for increasing the refractive index of the adhesive layer: a method in which 20 parts by weight or more of methyl acrylate monomer is included out of a total of 100 parts by weight of the main component (meth)acrylate monomer, and a method in which a (meth)acrylate monomer having an aromatic group is copolymerized. Although each method can be used alone, it is more preferable to use the two methods in combination.

[0025] In the pressure-sensitive adhesive composition of the present invention, the acrylic polymer does not contain a carboxyl group-containing copolymerizable vinyl monomer as the functional group-containing monomer, but contains a hydroxyl group-containing copolymerizable vinyl monomer. As the functional group-containing monomer, only the hydroxyl group-containing copolymerizable vinyl monomer may be used.

[0026] Examples of the hydroxyl group-containing copolymerizable vinyl monomer include at least one of hydroxyl group-containing alkyl (meth)acrylates such as 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate; and hydroxyl group-containing (meth)acrylamides such as N-hydroxy(meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-hydroxyethyl (meth)acrylamide. Among them, it is preferable that the hydroxyl group-containing copolymerizable vinyl monomer is at least one selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate. In addition, in the pressure-sensitive adhesive layer according to the present invention, the hydroxyl group-containing copolymerizable vinyl monomer contained in the pressure-sensitive adhesive composition can be used as a copolymerizable monomer for reducing the content of the carboxyl group-containing copolymerizable vinyl monomer, which is believed to affect the corrosiveness of the resulting pressure-sensitive adhesive layer against a corrodible adherend such as the ITO surface of a transparent conductive film. Therefore, the hydroxyl group-containing copolymerizable vinyl monomer can be used to improve the adhesive strength of the pressure-sensitive adhesive layer and reduce the corrosiveness. In the pressure-sensitive adhesive layer according to the present invention, the hydroxyl group-containing copolymerizable vinyl monomer contained in the pressure-sensitive adhesive composition is preferably 0.1 to 3.5 parts by weight out of a total of 100 parts by weight of the (meth)acrylate monomer, which is the main component.

[0027] The acrylic polymer of the pressure-sensitive adhesive composition used in the pressure-sensitive adhesive layer of the present invention is a copolymer having an acid value of 0.1 or less and a weight average molecular weight of 1,000,000 or more, the copolymer containing (1) as a main component (meth)acrylate monomer at least one selected from the group of monomers consisting of alkyl (meth)acrylate monomers having an alkyl group carbon number of C1 to C14 and (meth)acrylate monomers having an aromatic group, at least 30 parts by weight or more of butyl acrylate out of a total of 100 parts by weight of the main component (meth)acrylate monomers, and no carboxyl group-containing copolymerizable vinyl monomer, and the copolymer containing (2) 0.1 to 3.5 parts by weight of a hydroxyl group-containing copolymerizable vinyl monomer relative to a total of 100 parts by weight of the main component (meth)acrylate monomers.

[0028] The polymerization method for the copolymer is not particularly limited, and any known polymerization method such as solution polymerization, emulsion polymerization, etc. can be used as appropriate. The acrylic polymer preferably contains 50 to 100% by weight of an acrylic monomer such as a (meth)acrylate monomer or a (meth)acrylamide.

[0029] The properties of the pressure-sensitive adhesive composition, such as required physical properties, can be adjusted by blending a crosslinking agent and / or any appropriate additives with the acrylic polymer. (3) Examples of the crosslinking agent include at least one of polyisocyanate compounds such as biuret modified or isocyanurate modified diisocyanates such as hexamethylene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, tolylene diisocyanate, and xylylene diisocyanate, and adducts with trivalent or higher polyols such as trimethylolpropane and glycerin. The acrylic polymer preferably has a hydroxyl group as a functional group capable of crosslinking with the isocyanate compound of the crosslinking agent, and preferably contains a monomer having such a functional group in a side chain. The pressure-sensitive adhesive composition preferably contains 0.01 to 0.8 parts by weight of an isocyanate compound relative to 100 parts by weight of the total of the (meth)acrylate monomers of the main component. (3) Only an isocyanate compound may be used as the crosslinking agent. As the isocyanate compound, an adduct of tolylene diisocyanate is preferred, and an adduct of tolylene diisocyanate and trimethylolpropane is particularly preferred.

[0030] The pressure-sensitive adhesive composition preferably further contains (4) a silane coupling agent. (4) The silane coupling agent is a compound having at least one organic functional group and at least one hydrolyzable group in one molecule, the hydrolyzable group being an alkoxy group or the like bonded to a silicon atom. The silane coupling agent preferably has at least one organic functional group selected from the group consisting of an epoxy group, a (meth)acryloxy group, a mercapto group, and an amino group. Here, the (meth)acryloxy group means an acryloxy group (CH2=CHCOO-) or a methacryloxy group (CH2=C(CH3)COO-).

[0031] Examples of silane coupling agents having an epoxy group include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 5,6-epoxyhexyltrimethoxysilane, 5,6-epoxyhexylmethyldimethoxysilane, 5,6-epoxyhexylmethyldiethoxysilane, and 5,6-epoxyhexyltriethoxysilane. Examples of silane coupling agents having a (meth)acryloxy group include 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, 3-(meth)acryloxypropyldimethylethoxysilane, and 3-(meth)acryloxypropyldimethylmethoxysilane. Examples of the silane coupling agent having a mercapto group include 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, and 3-mercaptopropyltriethoxysilane. Examples of silane coupling agents having an amino group include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-(methylamino)propyltrimethoxysilane, and 3-(methylamino)propyltriethoxysilane. Furthermore, alkoxy oligomers (silicone alkoxy oligomers) containing the above organic functional groups and oligomerized can also be used as silane coupling agents.

[0032] (4) The content of the silane coupling agent is preferably 0.01 to 0.5 parts by weight per 100 parts by weight of the total of the (meth)acrylate monomers as the main component.

[0033] Other optional components include known additives such as antioxidants, surfactants, hardening accelerators, plasticizers, fillers, crosslinking catalysts, crosslinking retarders, hardening retarders, processing aids, and antiaging agents. These may be used alone or in combination of two or more.

[0034] The pressure-sensitive adhesive layer of the present invention can be obtained by applying the pressure-sensitive adhesive composition to a substrate or a release film, and then crosslinking the pressure-sensitive adhesive composition. The gel fraction of the pressure-sensitive adhesive layer after crosslinking is preferably 40 to 75%. When used for bonding between layers of optical components, a thin adhesive layer is desirable, and the thickness of the adhesive layer is preferably 1 μm to 25 μm, and more preferably 5 μm to 25 μm. Generally, the adhesive strength of an adhesive layer is approximately proportional to the thickness of the adhesive layer, and an adhesive layer having a thickness of 25 μm is preferably 1.5 to 6.0 N / 25 mm. Furthermore, after the adhesive layer is bonded to an adherend, the adhesive strength after 10 days at 70° C. is preferably 1.5 to 10 N / 25 mm. Examples of the adherend include glass plates such as alkali-free glass, and resin films.

[0035] When the pressure-sensitive adhesive layer according to the present invention is used for bonding between layers of optical members, it is desirable that the difference in refractive index between the pressure-sensitive adhesive layer and the optical member is as small as possible in order to reduce the reflection of light at the interface between the pressure-sensitive adhesive layer and the optical member. For this reason, the refractive index of the pressure-sensitive adhesive layer is preferably 1.47 to 1.50.

[0036] The pressure-sensitive adhesive film of the present invention can be produced by forming the pressure-sensitive adhesive layer of the present invention on one side of a substrate or a release film. As the base film used for forming the pressure-sensitive adhesive layer and the release film (separator) for protecting the adhesive surface, a resin film such as a polyester film can be used. The substrate film may be subjected to an antifouling treatment using a silicone-based or fluorine-based release agent or coating agent, or silica microparticles or the like, or an antistatic treatment by coating or kneading an antistatic agent, on the side opposite to the side on which the pressure-sensitive adhesive layer of the resin film is formed.

[0037] The surface of the release film that faces the adhesive surface of the adhesive layer is subjected to a release treatment using a silicone-based or fluorine-based release agent. A "release film / adhesive layer / release film" configuration can be achieved by combining the release-treated surfaces of a release film on both sides of a single adhesive layer. In this case, the release films on both sides are peeled off sequentially or simultaneously to expose the adhesive surface, making it possible to attach it to an optical component such as an optical film. Examples of optical films include polarizing films, retardation films, anti-reflection films, anti-glare films, ultraviolet absorbing films, infrared absorbing films, optical compensation films, and brightness enhancing films.

[0038] The adhesive film of the present invention can be used to bond various optical films for peripheral components of liquid crystal display devices, mainly polarizing plates, various optical films for touch panels, various optical films for electronic paper, various optical films for organic electroluminescence (EL) displays, and the like. In addition, the optical film may be an optical film with a pressure-sensitive adhesive layer, in which the pressure-sensitive adhesive layer is laminated on at least one surface of the optical film.Specific examples of the optical film include structures such as "optical film / pressure-sensitive adhesive layer / optical film", "optical film / pressure-sensitive adhesive layer / release film", "optical film / pressure-sensitive adhesive layer", "optical film / pressure-sensitive adhesive layer / optical film / pressure-sensitive adhesive layer / optical film", "optical film / pressure-sensitive adhesive layer / optical film / pressure-sensitive adhesive layer / release film", and "release film / pressure-sensitive adhesive layer / optical film / pressure-sensitive adhesive layer / release film". For example, in the case of "optical film / adhesive layer / release film" having an adhesive layer protected by a release film, the release film can be peeled off to expose the adhesive layer as in "optical film / adhesive layer", and then laminated with another optical film, thereby obtaining a configuration such as "optical film / adhesive layer / optical film" in which the adhesive layer is used for interlayer bonding. The pressure-sensitive adhesive film of the present invention is preferably used for bonding a polarizing plate and a display panel. For example, it is used as a pressure-sensitive adhesive layer of a polarizing plate with a pressure-sensitive adhesive layer. A retardation film having a phase difference of λ / 4 or λ / 2 may be used as a constituent material of the polarizing plate. EXAMPLES

[0039] The present invention will now be described in detail with reference to examples.

[0040] <Production of acrylic polymer> [Example 1] Nitrogen gas was introduced into a reactor equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, and the air in the reactor was replaced with nitrogen gas. Then, 100 parts by weight of butyl acrylate, 0.2 parts by weight of 8-hydroxyoctyl acrylate, and 60 parts by weight of a solvent (ethyl acetate) were added to the reactor. Then, 0.1 parts by weight of azobisisobutyronitrile as a polymerization initiator was dropped over 2 hours, and the mixture was reacted at 65°C for 6 hours to obtain an acrylic polymer solution 1 used in Example 1 having a weight average molecular weight of 1,000,000 or more. A portion of the acrylic polymer was collected and used as a sample for measuring the acid value described below. [Examples 2 to 5 and Comparative Examples 1 to 3] The acrylic polymer solutions used in Examples 2 to 5 and Comparative Examples 1 to 3 were obtained in the same manner as the acrylic polymer solution 1 used in Example 1, except that the monomer compositions were as shown in Groups (1) and (2) of Table 1. Although no particular measurement results are shown, the weight average molecular weights of the acrylic polymers contained in the acrylic polymer solutions of Examples 2 to 5 and Comparative Examples 1 to 3 were 1,000,000 or more.

[0041] <Production of Pressure-Sensitive Adhesive Composition, Pressure-Sensitive Adhesive Layer, and Pressure-Sensitive Adhesive Film> [Example 1] To the acrylic polymer solution 1 of Example 1 produced as described above, 0.2 parts by weight of Coronate L (a trimethylolpropane (TMP) adduct of a tolylene diisocyanate (TDI) compound) and 0.05 parts by weight of KBM-403 (3-glycidoxypropyltrimethoxysilane) were added and stirred to obtain an adhesive composition of Example 1. This adhesive composition was applied onto a release film made of a polyethylene terephthalate (PET) film coated with a silicone resin, and then dried at 90° C. to remove the solvent. The adhesive film was then aged for 7 days under an atmosphere of 23° C. and 50% RH to obtain an adhesive film of Example 1 having an adhesive layer of 25 μm in thickness formed by crosslinking the adhesive composition on one side of the release film. [Examples 2 to 5 and Comparative Examples 1 to 3] The pressure-sensitive adhesive films of Examples 2 to 5 and Comparative Examples 1 to 3 were obtained in the same manner as the pressure-sensitive adhesive film of Example 1 above, except that the compositions of the additives were as shown in Groups (3) and (4) of Table 1, respectively.

[0042] [Table 1]

[0043] In Table 1, the addition ratios of groups (2) to (4) are shown in parts by weight enclosed in parentheses, with the total of group (1) being 100 parts by weight. The compound names of the abbreviations of each component used in Table 1 are shown in Table 2. Coronate (registered trademark) L is a product name of Nippon Polyurethane Industry Co., Ltd., D-110N is a product name of Mitsui Chemicals, Inc., and KBM-403 and KBM-803 are product names of Shin-Etsu Chemical Co., Ltd. TDI means tolylene diisocyanate, TMP means trimethylolpropane, and XDI means xylylene diisocyanate. In Tables 1 and 2, carboxyl group-containing copolymerizable vinyl monomers are listed in group (2) together with hydroxyl group-containing copolymerizable vinyl monomers.

[0044] [Table 2]

[0045] <Test methods and evaluation> The release film (silicone resin-coated PET film) was peeled off from the pressure-sensitive adhesive film in Examples 1 to 5 and Comparative Examples 1 to 3 to expose the pressure-sensitive adhesive layer, which was then transferred to one side of a polarizing plate (film).

[0046] <Method of measuring adhesive strength> A 25 μm thick adhesive layer was transferred onto one side of a 180 μm thick polarizing plate (film) to obtain an adhesive film (optical film with an adhesive layer) as a sample. The obtained adhesive film was laminated with a pressure roller to the non-tin side of alkali-free glass that had been cleaned with acetone, and then autoclaved at 50°C, 0.5 MPa for 20 minutes, and then returned to an atmosphere of 23°C and 50% RH for 1 hour. The peel strength of the adhesive film was then measured using a tensile tester in accordance with JIS Z0237 "Test method for adhesive tapes and adhesive sheets," and the peel strength when peeled in a 180° direction at a speed of 300 mm / min was taken as the adhesive strength of the adhesive layer of the adhesive film (N / 25 mm).

[0047] <Acid value measurement method> The acid value of the acrylic polymer was measured by dissolving the sample in a solvent (a mixture of diethyl ether and ethanol in a volume ratio of 2:1) and titrating it with an automatic potentiometric titrator (Kyoto Electronics Manufacturing Co., Ltd., AT-610) using a 0.1 mol / l potassium hydroxide ethanol solution. The amount of potassium hydroxide ethanol solution required to neutralize the sample was measured. The acid value was then calculated using the following formula. Acid value = (B × f × 5.611) / S B = Amount (ml) of 0.1 mol / l potassium hydroxide ethanol solution used in titration f=factor of 0.1 mol / l potassium hydroxide ethanol solution S = mass of solids in the sample (g)

[0048] <Method of measuring gel fraction> After aging, the mass of the measurement sample before bonding to the polarizing plate was accurately measured, and it was immersed in toluene for 24 hours and then filtered through a 200-mesh wire screen. The filtered material was then dried at 100°C for 1 hour, and the mass of the residue was accurately measured to calculate the gel fraction of the adhesive layer (adhesive after crosslinking) using the following formula. Gel fraction (%) = insoluble portion mass (g) / adhesive mass (g) × 100

[0049] <Durability test method> A 10 cm square adhesive film prepared in the same manner as in measuring the adhesive strength was attached to the non-tin side of alkali-free glass in the same manner to create a sample.The sample was then left in a specified atmosphere (80°C dry atmosphere, or 60°C x 90% RH atmosphere) for 250 hours, then removed from the sample and placed in a 23°C x 50% RH atmosphere. After 1 hour, the condition of the adhesive film was visually observed to determine its durability. ○ The adhesive film does not peel off or foam at all. △: Peeling and bubbling have occurred in some parts of the adhesive film. × Peeling and bubbling have occurred over the entire adhesive film.

[0050] <Reworkability test method> A 10 cm square adhesive film prepared in the same manner as in the adhesive strength measurement was attached to the non-tin side of alkali-free glass in the same manner to create a sample. The sample was left in an atmosphere of 70°C for 10 days, then removed to an atmosphere of 23°C and left for 1 hour, after which the adhesive strength of the adhesive film was measured to determine its reworkability. ○The adhesive strength after 10 days at 70℃ is 1.5~10N / 25mm. △ The adhesive strength after 10 days at 70℃ is greater than 10N / 25mm but less than 20N / 25mm. × The adhesive strength after 10 days at 70℃ is greater than 20N / 25mm (cannot be peeled off).

[0051] The evaluation results are shown in Table 3. Regarding the acid value, it was confirmed that the acrylic polymers of Examples 1 to 5 and Comparative Examples 2 and 3, which do not contain a carboxyl group-containing copolymerizable vinyl monomer, have an acid value of 0.1 or less, and the acrylic polymer of Comparative Example 1, which contains a carboxyl group-containing copolymerizable vinyl monomer, has an acid value of more than 0.1.

[0052] [Table 3]

[0053] The adhesive films of Examples 1 to 5 had an adhesive strength of 1.5 to 6.0 N / 25 mm for a 25 μm thick adhesive layer, and a gel fraction of the adhesive layer after crosslinking of 40 to 75%, and thus had excellent adhesion and durability. In addition, the adhesive strength after 10 days at 70°C after lamination to an adherend was in the range of 1.5 to 10 N / 25 mm, and thus had excellent reworkability. In other words, the adhesive films of Examples 1 to 5 were able to overcome the requirements and problems.

[0054] The adhesive film of Comparative Example 1 did not contain butyl acrylate as the main component (meth)acrylate monomer, but contained a carboxyl group-containing copolymerizable vinyl monomer as the functional group-containing monomer. Perhaps due to the high gel fraction, the adhesive strength of the 25 μm-thick adhesive layer was strong, but the durability and reworkability in an atmosphere of 60°C x 90% RH were poor. The adhesive film of Comparative Example 2 had poor durability in an atmosphere of 60°C x 90% RH, and was also somewhat poor in durability and reworkability in an 80°C dry atmosphere, probably because the amount of hydroxyl-containing copolymerizable vinyl monomer in the adhesive composition was too high, resulting in a high gel fraction. In the adhesive film of Comparative Example 3, since the adhesive composition does not contain a carboxyl group-containing copolymerizable vinyl monomer or a hydroxyl group-containing copolymerizable vinyl monomer, the acrylic polymer is not crosslinked, the gel fraction is 0, and the adhesive strength of the adhesive layer with a thickness of 25 μm is very strong. As a result, the durability and reworkability were poor. As described above, the pressure-sensitive adhesive films of Comparative Examples 1 to 3 were unable to overcome the conventional requirements and problems.

Claims

1. A method for producing an optical film with a pressure-sensitive adhesive layer using a pressure-sensitive adhesive film in which a pressure-sensitive adhesive layer formed by crosslinking a pressure-sensitive adhesive composition containing an acrylic polymer and a crosslinking agent is laminated on one side of a release film, The acrylic polymer is (A) 100 parts by weight in total of at least one monomer selected from the group consisting of alkyl (meth)acrylate monomers having an alkyl group with a carbon number of C1 to C14 and (meth)acrylate monomers having an aromatic group; (B) an acrylic polymer which is a copolymer having an acid value of 0.1 or less and a weight average molecular weight of 1,000,000 or more, obtained by copolymerizing 0.1 to 3.5 parts by weight of a hydroxyl group-containing copolymerizable vinyl monomer without containing a carboxyl group-containing copolymerizable vinyl monomer and an amino group-containing (meth)acrylate; (A) contains at least one monomer selected from the group consisting of alkyl (meth)acrylate monomers having an alkyl group carbon number of C1 to C14 and (meth)acrylate monomers having an aromatic group, and contains at least 30 parts by weight of butyl acrylate and 20 parts by weight of methyl acrylate monomer, the (B) hydroxyl group-containing copolymerizable vinyl monomer is at least one selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate, the pressure-sensitive adhesive composition further comprises 0.01 to 0.8 parts by weight of an isocyanate compound as the crosslinking agent and 0.01 to 0.5 parts by weight of a silane coupling agent relative to 100 parts by weight in total of (A) at least one selected from the group of monomers consisting of alkyl (meth)acrylate monomers having an alkyl group with a carbon number of C1 to C14 and (meth)acrylate monomers having an aromatic group, The thickness of the pressure-sensitive adhesive layer is 1 to 25 μm, A method for producing an optical film with a pressure-sensitive adhesive layer, comprising peeling off the release film and transferring the pressure-sensitive adhesive layer onto one side of the optical film.

2. The method for producing a pressure-sensitive adhesive layer-attached optical film according to claim 1 , wherein the optical film is a polarizing plate.

Citation Information

Patent Citations

  • Optical component and projector

    JP2006293281A

  • Adhesive composition for optics, adhesive layer for optics, optical member with adhesive layer, method for producing the same and image display device

    JP2007084762A

  • Adhesive composition and laminate obtained by using the same

    JP2009091522A

  • Self-adhesive sheet

    JP2011153169A

  • Pressure-sensitive adhesive, pressure-sensitive adhesive for optical member, optical member with pressure-sensitive adhesive layer and image display device

    JP2012021148A